Comparative efficacy of modified Shiraki procedure and pedicled Island preputial flap in the treatment of severe concealed penis in children - Rifang Pan; Junzhong Li; Zhaowei Zhou; Kunlan Liang; Zhaopan Li; Zhihua Xiao (Scientific Reports)
Abstract To evaluate the clinical efficacy, advantages, and disadvantages of the modified Shiraki procedure and the transverse pedicled island flap phalloplasty in treating severe concealed penis in children. This study included seventy children with severe concealed penis treated at Yulin First People’s Hospital from June 2021 to January 2024. They were randomly assigned to either the observation group (n = 35), undergoing the modified Shiraki procedure, or the control group (n = 35), receiving the transverse pedicled island flap phalloplasty. We assessed average operation time, intraoperative blood loss, penile elongation, time until resolution of penile prepuce edema, flap infection or necrosis, penile erectile pain, prepuce skin redundancy, penile retraction, and overall penile appearance score six months postoperatively. The observation group showed significantly better average operative time and intraoperative blood loss compared to the control group (p < 0.05). The time for foreskin edema to regress was longer in the observation group (p < 0.05). No significant differences were noted in penile lengthening between groups (p > 0.05). The observation group had seven cases of refractory inner prepuce plate swelling and skin redundancy post-operation; two of these cases required secondary surgery, and without skin flap infection or necrosis. The control group reported one case of postoperative hemorrhage and four cases of infection and necrosis of the transferred flap, all resolved after prolonged dressing changes, with one case requiring surgical correction for scar contracture on the side of the penis. Neither group experienced penile erectile pain or retraction. Total complications and reoperations were similar between the groups. No significant difference in the overall penile appearance score was observed between the two groups six months post-surgery (p > 0.05). Both the modified Shiraki procedure and the transverse pedicled island flap phalloplasty are effective for treating severe concealed penis in children. The former is characterized by shorter, simpler operations, while the latter offers better cosmetic outcomes despite its complexity.